Mean Lives, Mean Laws : Oklahoma's Women Prisoners - Sharp, Susan F., 1951- (Book collections on Project MUSE., 2014)
Oklahoma has long held the dubious honor of having the highest female incarceration rate in the country, nearly twice the national average. In this compelling new book, sociologist Susan Sharp sets out to discover just what has gone so wrong in the state of Oklahoma-and what that might tell us about trends in female incarceration nationwide. The culmination of over a decade of original research, Mean Lives, Mean Laws exposes a Kafkaesque criminal justice system, one that has no problem with treating women as collateral damage in the War on Drugs or with stripping female prisoners of their.